Coordination of Piano‐Stool Complexes to a Hydrogen‐Bonded Rosette‐Type Assembly. Issue 25 (6th July 2017) - Zhang, Fan; Therrien, Bruno
Abstract : A new melamine (ME)–barbituric acid (BA) rosette‐type system has been prepared and characterized. The introduction of a pyridyl group on the barbituric acid moiety allows coordination of metal ions at the periphery of the ME3 · BA3 rosette. Reactions of 1.5 equiv. of [Ru(cym)Cl2 ]2 (cym = p ‐cymene) or [M(Cp*)Cl2 ]2 (Cp* = pentamethylcyclopentadienyl; M = Rh, Ir) with the rosette afford the corresponding ME3 · [BARu(cym)Cl2 ]3 and ME3 · [BAM(Cp*)Cl2 ]3 assemblies. The neutral metal‐containing rosettes ME3 · [BARu(cym)Cl2 ]3 and ME3 · [BARh(Cp*)Cl2 ]3 can also be obtained by adding the mononuclear complexes [BARu(cym)Cl2 ] and [BARh(Cp*)Cl2 ] to N, N′ ‐bis(4‐ tert ‐butylphenyl)melamine in chloroform. In addition, the triphenylphosphine derivatives [Ru(cym)(PPh3 )Cl2 ] or [M(Cp*)(PPh3 )Cl2 ] react with ME3 · BA3 in the presence of silver triflate to generate the ionic rosette‐type assemblies ME3 · [BARu(cym)(PPh3 )Cl + ]3 · 3CF3 SO3 – and ME3 · [BAM(Cp*)(PPh3 )Cl + ]3 · 3CF3 SO3 –, respectively. Abstract : Rosette‐type assemblies mixing covalent, coordination, hydrogen‐bond, and ionic interactions have been synthesized and characterized, providing a new strategy for the preparation of metal‐containing supramolecular assemblies.